Advancing the prediction and prevention of murder-suicide. Issue 3 (9th July 2018) - Podlogar, Matthew C.; Gai, Anna R.; Schneider, Matthew; Hagan, Christopher R.; Joiner, Thomas E.
Abstract : Purpose: The phenomenon of murder-suicide (aka. homicide-suicide) makes a sizeable impact on current public perceptions and policies regarding mental illness and risk for violence. However, within the past 25 years, our understanding of murder-suicide has remained relatively stable, and so has our relative inability to reliably predict and prevent it. The purpose of this paper is to propose pathways for furthering a cogent understanding of murder-suicide that may inform specific predictive and preventative practices. Design/methodology/approach: Research literature regarding empirical and theoretical positions in the fields of murder-suicide, homicide, and suicide are reviewed and discussed. Findings: While murder-suicide has many similarities to both homicide and suicide, no current theories of either alone have been successful in fully incorporating the phenomenon of murder-suicide. Theories specific to murder-suicide as a unique form of violence are in need of further research. Originality/value: Developing and empirically testing theories of murder-suicide may lead to a vast and needed improvement of our understanding, prediction, and prevention of these tragedies.